OPTIMASI FORMULA PATCH KOSMETIK EKSTRAK METANOL DAUN PACAR AIR (Impatiens balsamina L.) DENGAN KOMBINASI MATRIKS HPMC DAN POLIETILEN GLIKOL 400 SECARA SIMPLEX LATTICE DESIGN - Yovina Ika Adiaswati; Dian Puspitasari; Disa Andriani (Jurnal Insan Farmasi Indonesia, 2020)
Pacar air leaves contain coumarin compounds, flavonoids, quinones, and saponins which are known to have antibacterial activity. The purpose of this study was to determine the optimum proportion of the combination of HPMC and Propylene Glycol 400 and to determine the antibacterial activity of the methanol extract patch of pacar air leaves. Extraction using the maceration method with methanol. Optimization is done using the simplex lattice design, tested for physical quality. The optimum formula is then verified using the T-test. Antibacterial activity test of patch preparations was carried out by looking at the size of the inhibition zone, the inhibition diameter data obtained were processed with ANOVA statistics. The results of this research were the patch formula with a combination of HPMC (11.25 grams) and PEG 400 (3.75 grams). PEG 400 cannot be used singly because it cannot be solid. The results of the activity test of the methanol extract of the leaves of water henna against the Staphylococcus epidermidis bacteria showed that the average diameter of the inhibition zone was 15.16 ± 0.75mm. The results of one way ANOVA test obtained data of 0.096> 0.05, indicating that the positive control with the sample was not significantly different.